Failed grandparent parenting from a positive psychology perspective - Rahmatullah, Azam Syukur; Laili, Nurul Fithriyah Awaliatul (Universitas Islam Negeri Raden Intan Lampung, 2023)
The phenomenon of workers looking for work in big cities or abroad is rife in Indonesia, also known as migration. So workers care for their children by entrusting them to their grandparents at home. This study explores the upbringing of grandparents who are considered to have failed in nurturing their grandchildren in Puring District, Kebumen. The method used is a phenomenological study with a qualitative approach. Data collection techniques using observation, in-depth interviews with three grandmothers, and analysis phenomenologically reductive. The results of this study indicate that residents of Puring District, Kebumen are one of the areas where residents migrate as laborers. The care for the children of migrating workers is passed on to grandmothers at home without any parenting knowledge. The failure of parenting grandparents is caused by a form of parenting based on fear, ignorance/neglect, and parenting without exemplar, resulting in the behavior of grandchildren who are lazy, spoiled, rarely worship, rude speech style, and promiscuity